تقويم الأداء بمكاتب التسجيل والامتحانات بكليات القطاع الصحي بجامعة الجزيرة (السودان) - علي, د. مالك النعيم محمد; أحمد مصباح, أ. سهير حيدر محمد; بابكر, بروف. حيدر الهادي (Gezira Journal of Health Sciences, 2017)
تعد مكاتب التسجيل والامتحانات من أهم المكاتب بكليات الجامعة ولها دور أساسي في تطبيق فلسفة الجامعة وتحقيق رسالتها وذلك لارتباطها بالعملية التعليمية التي تمثل الوظيفة الأساسية للجامعة. هدفت هذه الدراسة إلى تقييم الوضع الراهن لأداء مكاتب التسجيل والامتحانات بكليات القطاع الصحي بجامعة الجزيرة وذلك من خلال قياس مدى رضا الطلاب وأعضاء هيئة التدريس عن أداء هذه المكاتب، و تحديد تحديات سير العمل بها، إضافة إلى تحديد الاحتياجات التدريبية للعاملين بتلك المكاتب. استخدم الباحثون المنهج الوصفي التحليلي، والاستبانة كأداة للدارسة، وكذلك تم استخدام مقياس ليكارت الخماسي لدراسة الاستبيان لتحديد العلاقات. خُلصت الدراسة إلى رضا أعضاء هيئة التدريس عن أداء مكاتب التسجيل والامتحانات بدرجة عالية، ورضا الطلاب كان بدرجة متوسطة. أوضحت الدراسة أن طباعة الامتحانات تتم بسرية تامة، وأن وظيفة ضابط التسجيل والامتحانات تتطلب التفرغ التام. من تحديات سير العمل الآتي: لا يتم تنفيذ المقررات وعقد الامتحانات وفق الجدول الزمني المحدد في أحايين كثيرة ، وتأخر استلام نتائج الامتحانات، وعدم توفر المعينات الكافية للعمل، وتكدس الأوراق المكاتب مع عدم وجود نظام للأرشفة، كذلك أوضحت الدراسة نقص القاعات، و حاجة العاملين لدورات تدريبية في لوائح الدراسات الجامعية و برامج التسجيل الإلكتروني والنتائج، ومقررات في اللغة الانجليزية. أوصى الباحثون بالآتي: التزام الكليات بالتقويم الدراسي المجاز، تسليم نتائج امتحانات المقررات للطلاب خلال أسبوعين من نهاية الفصل الدراسي، زيادة عدد القاعات وتأهيلها، وإنشاء قاعة خاصة بالامتحانات، والتوجه التام نحو العمل الإلكتروني، وأن تكون وظائف ضباط التسجيل والامتحانات ومساعديهم وظائف مستقلة، وأن تعقد دورات تدريب دورية للعاملين وخاصة في برامج الحاسوب والتسجيل والنتائج الإلكترونية. كذلك توصي الدراسة بإعادة دراسات مماثلة تحلل العمل بكل مكتب على حدة لاختلاف وخصوصية المنهج في هذه الكليات The registration and examination offices are considered to be one of the most important units in the university faculties. Their role ensure the application of philosophy of the university and achieving its mission, because of their direct link with the educational process the main target of the university establishment. This study aimed to evaluate the current status of performance of the registration and examination offices in the faculties of the health sector at Gezira University. The method was conducted through identifying the extent of teaching staff and students' satisfaction about the performance of these offices, identifying challenges of work, in addition to identifying the training needs for the staff in these offices. The researchers used the descriptive analytical method, and questionnaire as a research tool. Likert’s Scale was used to assess responses the questionnaire questions. The study results showed that the satisfaction of the teaching staff members with the performance of the registration and examination offices was at high degree. The students' satisfaction was at a moderate degree; the points that have been collectively agreed upon include: The examination is typed with extreme secrecy and the position of the registration and examination officer is extremely important and requires total dedication. The challenges that influence the work path include: curricula (modern course) and examination are not carried out according to the set timetable, delay in receiving examination results, the unavailability of adequate work facilities, piling up of papers in offices and absence of archiving system, shortage of exam halls, working staff need training courses on university regulations of undergraduate studies. Electronic registration and results program and English language courses. The researchers'  recommendations include the importance of faculties' commitment with the approved academic calendar, implementing courses according to the specified timetable, handel of courses examinations results to students within two weeks from the end of the semester, increasing the number of lecture halls and rehabilitate them, establishment of examination halls, the complete orientation towards working with electronic system, the post of need registration and examination officers and their assistants should be full-time jobs, and periodic training for the working staff especially in computer programs, registration and electronic results. Moreover more researches ae needed, to study in depth each health faculty office.